Okay, so what I think your (poorly formatted) working is showing is this:
\(\displaystyle \dfrac{\dfrac{1}{2}x+3}{100-100h} = \dfrac{\dfrac{1}{2}(100)+3 - \dfrac{1}{2}(100h)+3}{h}\)
Assuming the above is the correct interpretation of your work, I have a few questions. First, where did the number 100 come from? The problem you originally posted asked about the average rate of change between the points x=a and x=a+h. It appears as if you've somehow transformed that into the interval between the points x=100 and x=100h. By what basis have you concluded this? Second, by what basis have you concluded that the denominator, being 100-100h, is equal to h?